Monoterpenes Support Systemic Acquired Resistance within and between Plants. Issue 6 (23rd May 2017) - Riedlmeier, Marlies; Ghirardo, Andrea; Wenig, Marion; Knappe, Claudia; Koch, Kerstin; Georgii, Elisabeth; Dey, Sanjukta; Parker, Jane E.; Schnitzler, Jörg-Peter; Vlot, A. Corina
Abstract : Infection of Arabidopsis thaliana with avirulent Pseudomonas syringae induces camphene and α- and β-pinene emissions contributing to systemic resistance induction in the same and neighboring plants. Abstract: This study investigates the role of volatile organic compounds in systemic acquired resistance (SAR ), a salicylic acid (SA )-associated, broad-spectrum immune response in systemic, healthy tissues of locally infected plants. Gas chromatography coupled to mass spectrometry analyses of SAR -related emissions of wild-type and non-SAR -signal-producing mutant plants associated SAR with monoterpene emissions. Headspace exposure of Arabidopsis thaliana to a mixture of the bicyclic monoterpenes α-pinene and β-pinene induced defense, accumulation of reactive oxygen species, and expression of SA - and SAR-related genes, including the SAR regulatory AZELAIC ACID INDUCED1 ( AZI1 ) gene and three of its paralogs. Pinene-induced resistance was dependent on SA biosynthesis and signaling and on AZI1 . Arabidopsis geranylgeranyl reductase1 mutants with reduced monoterpene biosynthesis were SAR-defective but mounted normal local resistance and methyl salicylate-induced defense responses, suggesting that monoterpenes act in parallel with SA . The volatile emissions from SAR signal-emitting plants induced defense in neighboring plants, and this was associated with the presence of α-pinene, β-pinene, and camphene in the emissions of the "sender" plants. Our data suggest that monoterpenes, particularly pinenes, promote SAR, acting through ROS and AZI1, and likely function as infochemicals in plant-to-plant signaling, thus allowing defense signal propagation between neighboring plants.